Studi Awal Keanekaragaman Herpetofauna di Petungkriyono, Kabupaten Pekalongan,Propinsi Jawa Tengah - Eprilurahman, Rury (Masyarakat Zoologi Indonesia (Zoological Society of Indonesia), 2010)
The objectives of the research were to study the species diversity, species richness, species status and habitat preferences of herpetofauna in Petungkriyono, Pekalongan R egency, Central Java Province. The research was conducted since 10 July to 21 July 2009, using a variety of methods to sample the herpetofauna. The result showed 51 species of herpetofauna include into 15 family. They were 20 species of Amphibia, 16 species of Lacertilia and 15 species of Ophidia. Five of them were endemic to Java, namely lchthyophis sp., Huia masonii, Megoprhys montana, Rhacophorus margaritifer and Sphenomorphus puncticentralis. Unidentified and possibly undescribed species of unusual specimen referred to genus Limnonectes and Ichthyophis and still being examined.